Search for new sources of bioactive compounds in the flora of Southern Siberia and evaluation of the potential for their use - Alexander S. Revushkin; Evgenia A. Kasterova; Daria S. Chigodaikina; Larisa N. Zibareva (Acta Biologica Sibirica, 2023)
The paper addresses the issue of the search for plants containing bioactive compounds and evaluation of the potential for their use. A methodology and an algorithm have been developed to conduct comprehensive studies using methods of taxonomy and plant ecology, phytochemistry, botanical geography, and resource studies. The developed algorithm has been implemented for large taxa of the family Asteraceae Dumort. 1820 from the flora of Southern Siberia (tribe Cynareae Lam. ex DC. 1813 and genus Artemisia L., 1753). Four groups of plants were identified, and recommendations on their use were elaborated. The group of promising species included 20 representatives of the tribe Cynareae (from the genera Saussurea DC. 1979, Serratula L. 1753, Centaurea L. 1753, Cirsium Mill. 1754) and 15 species of the genus Artemisia. The algorithm enabled identification of 30 species of the tribe Cynareae and 8 species of the genus Artemisia that need special conservation measures.